Detection, quantification and morphological characterization of Vibrio cholerae indicator bacteriophages - Talledo, Miguel (1998)
The specificity between bacteriophages and bacteria is a feature that has been successfully used for the detection of several microbial species. For this reason the detection of vibriophages is a valuable research tool, and it might be a fast and convenient method to Vibrio cholerae diagnostics. The goal of this study was to detect vibriophages in shallow seawater samples and to determine the morphological characteristics of these vibriophages. It was determined the growth kinetics of a strain of Vibrio cholerae serotype Inaba. Seawater samples taken from five shallow points from an adjacent sector to La Chira beach, and Rímac and Chillón river mouths were analyzed qualitatively and quantitatively using different inoculum volumes and several incubation periods. The bacteriophages were concentrated and stained for the morphological study by transmission electron microscopy. The results we obtained indicate that the vibriophages could be an important tool as a Vibrio cholerae indicator.